Content and Accumulation of Macronutrients in Radish Seeds in Response to Sulfur and Organic Compost - Aguilar, Ariel Santivañez; Vasque, Henrique; Bardiviesso, Estefânia Martins; Acevedo, Andres Felipe Gaona; Felito, Ricardo Adriano; Pelvine, Raíra Andrade; Bezerra, Sara Raissa Brito; Leis, José Murillo de Oliveira; Cardoso, Antonio Ismael Inácio; Lemes, Ernane Miranda (Journal of Agricultural Studies, 2021)
Sulfur (S) is usually the second most accumulated nutrient in seeds of Cruciferae plant species such as the radish. Tropical soils have low S availability creating a challenge to manage plant nutrition and balanced plant development to produce high-quality seeds. This study evaluated the influence of S doses and organic compost fertilization on the content and accumulation of macronutrients in radish seeds. Eight treatments were studied in subdivided plots, where the presence (50 t ha-1) or absence of organic compost was placed in the main plot, and the S doses (0, 60, 120, 180 kg ha-1 of S) were placed in the subplots. A randomized block design with six replications was used. Seed dry weight, N, P, K, Ca, Mg, and S concentration (g kg-1 of dry matter), and the accumulation of nutrients in seeds (g plant-1) were evaluated. There was no significant effect of S doses, or organic compost, on the contents of macronutrients in radish seeds. When organic compost was not applied, great doses of S generated great dry weight and accumulation of macronutrients in the radish seeds. However, the application of organic compost increased the dry weight and the accumulation of all macronutrients in radish seeds in low S doses (up to 66 kg ha-1). Also, the presence of organic compost increased the dry weight and the concentration of macronutrients in radish seeds. The decreasing order of macronutrient content and accumulation by the radish seeds was: N > S > K > P > Ca > Mg.